Triggering Apoptotic Death of Human Malignant Melanoma A375.S2 Cells by Bufalin: Involvement of Caspase Cascade-Dependent and Independent Mitochondrial Signaling Pathways. (10th June 2012) - Hsiao, Yu-Ping; Yu, Chun-Shu; Yu, Chien-Chih; Yang, Jai-Sing; Chiang, Jo-Hua; Lu, Chi-Cheng; Huang, Hui-Ying; Tang, Nou-Ying; Yang, Jen-Hung; Huang, An-Cheng; Chung, Jing-Gung
Abstract : Bufalin was obtained from the skin and parotid venom glands of toad and has been shown to induce cytotoxic effects in various types of cancer cell lines, but there is no report to show that whether bufalin affects human skin cancer cells. The aim of this investigation was to study the effects of bufalin on human malignant melanoma A375.S2 cells and to elucidate possible mechanisms involved in induction of apoptosis. A375.S2 cells were treated with different concentrations of bufalin for a specific time period and investigated for effects on apoptotic analyses. Our results indicated that cells after exposure to bufalin significantly decreased cell viability, and induced cell morphological changes and chromatin condensation in a concentration-dependent manner. Flow cytometric assays indicated that bufalin promoted ROS productions, loss of mitochondrial membrane potential (Δ Ψ m ), intracellular Ca 2+ release, and nitric oxide (NO) formations in A375.S2 cells. Additionally, the apoptotic induction of bufalin on A375.S2 cells resulted from mitochondrial dysfunction-related responses (disruption of the Δ Ψ m and releases of cytochrome c, AIF, and Endo G), and activations of caspase-3, caspase-8 and caspase-9 expressions. Based on those observations, we suggest that bufalin-triggered apoptosis in A375.S2 cells is correlated with extrinsic- and mitochondria-mediated multiple signal pathways.